Future-Proofing Philippine Higher Education Toward 2050: Filipino Educators’ Roles - David, Rowena May T.; Maroma, Adrian P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explores the futures of Philippine higher education toward 2050. Using a qualitative–exploratory foresight approach, it employed STEEP analysis and Causal Layered Analysis (CLA) with data drawn from secondary sources such as policy papers, international reports, and scholarly works. The findings highlight artificial intelligence (AI) and modular learning as key opportunities for personalized and inclusive education. However, challenges persist in digital inequality, inadequate infrastructure, and limited faculty readiness. Sustainability integration is emerging but remains underdeveloped. The study recommends strengthening digital infrastructure, enhancing faculty capacity, adopting inclusive AI tools, and embedding sustainability in curricula. Public–private partnerships and anticipatory policies are essential to ensure a future-ready higher education system that equips Filipino learners for evolving societal and labor-market demands.